ChemInform Abstract: Experimental and Theoretical Investigations of Functionalized Boron Nitride as Electrode Materials for Li‐Ion Batteries. Issue 23 (May 2016) - Zhang, Fan; Nemeth, Karoly; Bareno, Javier; Dogan, Fulya; Bloom, Ira D.; Shaw, Leon L.
Abstract: Functionalized h‐BN (FBN) is obtained by reacting h‐BN with molten LiOH in a 1:1 molar ratio (stainless steel autoclave with Cu gasket, 500 °C, 8 h) followed by an intense ball milling of the product phase.